2015
DOI: 10.5296/ijl.v7i1.7199
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Functional Linguistics as Interpersonal Semantics: Appraisal and Attitude in the Stylistic Analysis of an English Novel

Abstract: Subsumed under Systemic Functional Linguistics (SFL) that emphasizes functionality of language in social contexts, Appraisal is a recent theoretical framework that extends the interpersonal dialogistic semantics dimension of SFL into interesting elaboration. This system, in turn, has three subsystems, one of which is Attitude which is geared to justifying and explaining the processes through which writers and speakers communicate their evaluations towards individuals, material objects and phenomena, or even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
1
20
1
1
Order By: Relevance
“…This study has given new information that appraisal can also be conducted on news item different from the other researches to show the kinds of affect to urge the world to pay attention to the kinds of feeling felt by the marginal sides (Palestinian). It also supports the statements stated by Wei,Wherrity, and Zhang (2015) as one of the proofs that appraisal is an appropriate tool to analyze the attitude and interpersonal meanings both in discourse like what have been conducted by Dong (2006); Pascual and Unger (2010); Isaac (2012); Hadidi and Parvin (2015); Drasovean and Tagg (2015) and in critical discourse conducted by Haristyanti (2015) on Obama's speech.…”
Section: Positivesupporting
confidence: 78%
See 1 more Smart Citation
“…This study has given new information that appraisal can also be conducted on news item different from the other researches to show the kinds of affect to urge the world to pay attention to the kinds of feeling felt by the marginal sides (Palestinian). It also supports the statements stated by Wei,Wherrity, and Zhang (2015) as one of the proofs that appraisal is an appropriate tool to analyze the attitude and interpersonal meanings both in discourse like what have been conducted by Dong (2006); Pascual and Unger (2010); Isaac (2012); Hadidi and Parvin (2015); Drasovean and Tagg (2015) and in critical discourse conducted by Haristyanti (2015) on Obama's speech.…”
Section: Positivesupporting
confidence: 78%
“…A large number of researches have conducted a study on appraisal and there is still a gap found. Dong (2006) investigated appraisal on students' writing in blog; Pascual and Unger (2010) focused on appraisal in proposals which got international grant; Isaac (2012) analyzed arguments of ten international non native speaker who uses English for academic purposes by using appraisal theory; Hadidi and Parvin (2015) conducted a study on appraisal in novel; Wei,Wherrity, and Zhang (2015) reviewed appraisal theory from the current research in China and abroad; Haristyanti (2015) saw appraisal used by Barack Obama in his speech; Drasovean and Tagg (2015) studied on online participants' comments. The study on appraisal by analyzing newspaper online in religion context in critical discourse analysis has not been done and it becomes the gap of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, Appraisal Theory was applied in the research of childbirth narratives (Page, 2003), high-and lowrated English argumentative essays by EFL students in two Chinese universities (Liu, 2013), English song discourses (Li, 2016), critical reading in teaching English at colleges (Ruo-mei, 2016), English novel discourse (Hadidi & Mohammadbagheri-Parvin, 2015) or President Xi's remarks at the press conference (Zhang, 2018).…”
Section: Introduction 1thementioning
confidence: 99%
“…Michael summarizes stylistic analysis as three interrelated steps: description, explanation and evaluation [4]. According to the structure of language, descriptive methods are divided into phonetic level, lexical level, semantic level, syntactic level and discourse level.…”
mentioning
confidence: 99%